1997
DOI: 10.1097/00006223-199711000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Nursing Students Evidence-Based Nursing

Abstract: Nurse educators face many challenges in the current healthcare environment. Educational methods, philosophies, and the content of curricula need to be reexamined to meet the needs of professional nurses who will practice in the next millennium. Evidence-based nursing is one approach that may enable future healthcare providers to manage the explosion of new literature and technology and ultimately may result in improved patient outcomes. The authors provide an introduction to evidence-based nursing as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…The clinical teacher promotes adult learning principles, facilitates critical thinking, sets the “tone,” and provides for smooth function of the clinical learning experience (13). Clinical teachers need teaching strategies that facilitate the students' immediate learning and encourage a lifelong pattern of learning (6). EBC is a model that promotes these goals.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical teacher promotes adult learning principles, facilitates critical thinking, sets the “tone,” and provides for smooth function of the clinical learning experience (13). Clinical teachers need teaching strategies that facilitate the students' immediate learning and encourage a lifelong pattern of learning (6). EBC is a model that promotes these goals.…”
Section: Introductionmentioning
confidence: 99%
“…The major focus of the curriculum revolution is the preparation of graduates with new and different perspectives and abilities, to face a rapidly changing healthcare environment 6 . It is suggested that the content of curricula needs to be re‐examined using an evidence‐based approach to meet the needs of professional nurses 7 …”
Section: The Comprehensive Systematic Reviewmentioning
confidence: 99%
“…• `Evidence‐based nursing is one approach that may enable future health care providers to manage the explosion of new literature and technology and ultimately may improve patient outcomes' (Kessenich et al . 1997, p. 25)…”
Section: The Meanings Attached To Evidence‐based Symbolismmentioning
confidence: 99%